PENERAPAN METODE ROLE PLAYING DALAM PEMBELAJARAN MENULIS TEKS EKSPLANASI PADA SISWA KELAS XI SMA NEGERI 1 SLIYEG - Komariah, Komariah; Sholeh, Muhammad; Naufal, Muji Zain (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
The low level of ability of students at SMA Negeri 1 Sliyeg in the 2023/2024 academic year in learning to write explanatory texts and the limitations of teachers in varying innovative and effective learning methods to improve students' skills in producing explanatory texts are the background for the author in conducting this research. The effort made by the researcher is to apply the role-playing learning method in learning to write explanatory texts. This study aims to: 1) determine whether the application of the role-playing method in learning to write explanatory texts for grade XI students of SMA Negeri 1 Sliyeg in the 2023/2024 academic year is effective and 2) describe how the learning activities of writing explanatory texts in the application of the role-playing method. This study used an experimental method with a nonequivalent control group design. The population of this study was all grade XI students of SMA Negeri 1 Sliyeg in the 2023/2024 academic year. Sampling using non-probability sampling technique with purposive sampling method was determined class XI MIPA 4 as the experimental class with 36 students and XI MIPA 5 as the control class with 36 students. Research data were collected through written tests and observation sheets. Based on the results of statistical calculations using two independent t-tests (independent simple t-test), the calculated t was 3.672 and the t table was 1.994. So t count (3.672) > t table (1.994), this indicates that H1 is accepted and H0 is rejected. Thus, the author concludes that the application of the role playing method in learning to write explanatory texts for class XI students of SMA Negeri 1 Sliyeg in the 2023/2024 academic year is effective. Based on the analysis of observation results, it is proven that the application of the role playing method can increase student activeness in the learning process of writing explanatory texts for class XI students of SMA Negeri 1 Sliyeg in the 2023/2024 academic year. ABSTRAKRendahnya tingkat kemampuan siswa SMA Negeri 1 Sliyeg Tahun Pelajaran 2023/2024 dalam pembelajaran menulis teks eksplanasi serta keterbatasan guru dalam mevariasikan metode pembelajaran yang inovatif dan efektif untuk meningkatkan keterampilan siswa dalam memproduksi teks eksplanasi melatarbelakangi penulis dalam melakukan penelitian ini. Upaya yang dilakukan peneliti yaitu dengan menerapkan metode pembelajaran role playing dalam pembelajaran menulis teks eksplanasi. Penelitian ini bertujuan untuk: 1) mengetahui apakah penerapan metode role playing dalam pembelajaran menulis teks eksplanasi pada siswa kelas XI SMA Negeri 1 Sliyeg Tahun Pelajaran 2023/2024 efektif dan 2) mendeskripsikan bagaimana aktivitas pembelajaran menulis teks eksplanasi dalam penerapan metode role playing. Penelitian ini menggunakan metode eksperimen dengan desain nonequivalen control group design. Populasi penelitian ini adalah seluruh siswa kelas XI SMA Negeri 1 Sliyeg Tahun Pelajaran 2023/2024. Pengambilan sampel menggunakan teknik non probability sampling dengan metode purposive sampling ditetapkan kelas XI MIPA 4 sebagai kelas eksperimen dengan jumlah 36 siswa dan XI MIPA 5 sebagai kelas kontrol dengan jumlah 36 siswa. Data penelitian dikumpulkan melalui tes tulis dan lembar observasi. Berdasarkan hasil penghitungan statistik dengan menggunakan uji t dua independen (independen simple t test), diperoleh thitung sebesar 3,672 dan ttabel sebesar 1,994. Jadi thitung (3,672) > ttabel (1,994), hal ini menunjukan bahwa H1 diterima dan H0 ditolak. Dengan demikian, penulis menyimpulkan bahwa penerapan metode role playing dalam pembelajaran menulis teks eksplanasi pada siswa kelas XI SMA Negeri 1 Sliyeg Tahun Pelajaran 2023/2024 efektif. Berdasarkan analisis hasil observasi, terbukti bahwa penerapan metode role playing dapat meningkatkan keaktifan siswa dalam proses pembelajaran menulis teks eksplanasi pada siswa kelas XI SMA Negeri 1 Sliyeg Tahun Pelajaran 2023/2024.